ChemInform Abstract: Stimuli Responsive Materials. Issue 46 (24th October 2013) - Theato, Patrick; Sumerlin, Brent S.; O'Reilly, Rachel K.; Epps, Thomas H. III
Abstract Review: special issue with 23 reviews; <1000 refs.